IDENTIFICATION OF ENVIRONMENTALLY FISHING GEAR OPERATING IN KAMPAR RIVER OF KUOK SUB-DISTRICT KAMPAR REGENCY. - Ade Rianasari; Bustari Bustari; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAKThe study was conducted in november through December 2017  in district Kuok regency Kampar Riau Province. This study aims to(1) identify  the environmentally friendly fishing gear in accordance with the FAO, (2) know the fishing gear that has the highest level of environmental friendliness. The method used is the survey method is with direct observation in the field and conducting interviews with fishermen,Collecting data using a questionnaire and analyzed using descriptive analysis of the results of the research described in graphic form, and tables. Based on field observations in the know that fishing gear used by fishermen in district Kuok regency Kampar is classified as a very enviromental friendly and eviromental friendly fishing gear. The results of this research showed that portabel trap, trap, vertical fishing line, giilnet, used bottle and fishing rod are a very enviromental friendly fishing gear, while lift net, scoop net, surrounding net, cast net, and harpoon are an enviromental friendly fishing gear.Keywords :Identification, Fishing gears, environmentally friendly.